2014
DOI: 10.1136/neurintsurg-2014-011237
|View full text |Cite
|
Sign up to set email alerts
|

Flow diverter stents for unruptured saccular anterior circulation perforating artery aneurysms: safety, efficacy, and short-term follow-up

Abstract: Our preliminary results show that flow diversion technology is an effective and safe therapy for complex, hard-to-treat aneurysms in perforating arteries. Larger studies with long-term follow-up are needed to validate our promising results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…4,6,24,37,40,46 These promising results led to increasing off-label use of the PED for aneurysms that are not large and not wide necked, and several groups have found similarly strong results after treating small aneurysms 11,17,26 and other off-label applications. 2,10,13,28,32,36 Still, the number of studies on use of the PED to treat small aneurysms has been limited, and very few have directly compared patient outcomes with those of patients after coiling or clipping. 30 The mean aneurysm size in this study was 8.2 mm, which is smaller than the minimum size (10 mm) for which the PED is approved.…”
Section: Discussionmentioning
confidence: 99%
“…4,6,24,37,40,46 These promising results led to increasing off-label use of the PED for aneurysms that are not large and not wide necked, and several groups have found similarly strong results after treating small aneurysms 11,17,26 and other off-label applications. 2,10,13,28,32,36 Still, the number of studies on use of the PED to treat small aneurysms has been limited, and very few have directly compared patient outcomes with those of patients after coiling or clipping. 30 The mean aneurysm size in this study was 8.2 mm, which is smaller than the minimum size (10 mm) for which the PED is approved.…”
Section: Discussionmentioning
confidence: 99%
“…A recent clinical study on intracranial perforators has shown results that further support our observations. 23 Additionally, in a recent CFD study in small-caliber human arteries, 17 a relatively low flow rate reduction of 8% was found after FDS jailing. In a recent animal study dealing with telescopic stenting, Dai et al 8 found patency of the jailed branches while at the same time acknowledging limitations regarding perforators.…”
Section: Study Limitationsmentioning
confidence: 96%
“…In a few human case series involving intracranial arterial perforators, 15,23 rare symptomatic occlusions in jailed branches were reported. Perforators are by definition terminal arteries and, according to our observations, are expected to remain patent after stenting.…”
Section: Study Limitationsmentioning
confidence: 99%
“…2 Numerous studies have since demonstrated the safety and efficacy of the PED in treating aneurysms with varying morphologies in different anatomic locations. [3][4][5][6][7][8] As the clinical indications for PED placement expand, predictors of radiographic outcomes have become a topic of ongoing investigation. Although 1 study found that fusiform aneurysm morphology and shorter follow-up length were independent predictors of incomplete occlusion, this study was limited by a small sample size and a mean follow-up of 6.1 months.…”
mentioning
confidence: 99%